Industrial cities : history and future - Zimmermann, Clemens 1951- Hrsg (Campus Verl, 2013)
Bringing together essays from leading experts who analyze how the landscapes, images, social dynamics, and economies of the industrial city have changed through boom and bust, this volume covers a wide range of subjects, from car cities to steel towns, from visualization of industrial cities in avant-garde art to the role of industrial heritage in urban regeneration. In total, 'Industrial Cities' makes a significant contribution to our understanding of how the past shapes the future; it will be of interest not only to urban and economic historians, but also to social geographers and policy makers